Jump‐starting coastal wetland restoration: a comparison of marsh and mangrove foundation species. Issue 5 (1st July 2019) - Yando, Erik S.; Osland, Michael J.; Jones, Scott F.; Hester, Mark W.
Abstract : During coastal wetland restoration, foundation plant species are critical in creating habitat, modulating ecosystem functions, and supporting ecological communities. Following initial hydrologic restoration, foundation plant species can help stabilize sediments and jump‐start ecosystem development. Different foundation species, however, have different traits and environmental tolerances. To understand how these traits and tolerances impact restoration trajectories, there is a need for comparative studies among foundation species. In subtropical and tropical climates, coastal wetland restoration practitioners can sometimes choose between salt marsh and/or mangrove foundation species. Here, we compared the early life history traits and environmental tolerances of two foundation species: (1) a salt marsh grass ( Spartina alterniflora ) and (2) a mangrove tree ( Avicennia germinans ). In an 18‐month study of a recently restored coastal wetland in southeastern Louisiana (USA), we examined growth and survival along an elevation gradient and compared expansion and recruitment rates. We found that the rapid growth, expansion, and recruitment rates of the salt marsh grass make it a better species for quickly establishing ecological structure at suitable elevations. The slower growth, limited expansion, and lower recruitment of the mangrove species show its restricted capacity for immediate structural restoration, especially in areas where it co‐occurs with perennial salt marsh species. Our findings suggest that the structural attributes needed in recently restored areas can be achieved sooner using fast‐growing foundation species. Following salt marsh grass establishment, mangroves can then be used to further assist ecosystem development. This work highlights how appropriate foundation species can help jump‐start ecosystem development to meet restoration objectives.